Arc Characteristics and Welding Process of Laser K-TIG Hybrid Welding - Hongchang Zhang; Jiang Yu; Zixiao Zhang; Jianguo Gao; Zhaofang Su; Zhaorong Sun; Yinan Li (Metals, 2022)
The Q235 steel plate butt joint was successfully welded by the laser K-TIG hybrid welding method. The effects of hybrid welding process parameters such as welding current, the distance between heat sources, laser power, laser defocusing amount, and welding speed on the coupled arc profile and welding process stability were studied. The results indicated that the laser deflects the K-TIG arc, and the deflection angle becomes smaller as the arc current increases. After K-TIG generates small holes, if the laser beam acts on the bottom of the keyhole, the welded depth can be further increased; however, the laser power has little effect on the welded depth. The distance between heat sources is the main factor affecting the state of laser-arc coupling. Optical microstructures of welded joints showed that the grains in the arc zone were coarser than those in the laser zone, and there are more columnar crystals in the fusion zone. The microhardness of the weld center is significantly higher than that of the base metal, up to 220 HV. At the same time, the change of tensile strength of the weld under the influence of a single parameter was analyzed, and it was found that tensile properties of the weld first increased and then decreased with the increase of K-TIG arc current I, heat source distance D, and welding speed V, respectively. With the increase of laser power P, it first decreased and then increased, and with the increase of laser defocusing amount <semantics>δ</semantics>f, it showed a downward trend.